Growing Potential: An Analysis of Legal and Policy Barriers Faced by Women in Horticulture in Guatemala, Nepal, Tanzania, & Zambia - Collinson, Erin; Habeel, Nadine; Jawaid, Fatima; Jean, Laura; Williams, Kari (Hubert H. Humphrey School of Public Affairs, 2013)
In 2009 the Horticulture Collaborative Research Support Program (CRSP) at the University of California, Davis was established as part of an effort to reduce rural poverty and chronic malnutrition. Horticulture production provides individuals and families with the opportunity to better their social and economic circumstances through income generation and improved nutrition and health. However, in both agriculture and horticulture women in many developing countries earn lower wages and have access to fewer resources compared to men, despite the fact that women provide much of the labor in these sectors. To support the work of the Horticulture CRSP this report identifies barriers that have the potential to limit the benefits of horticulture production for rural women in four countries: Guatemala, Nepal, Tanzania, and Zambia. This report is divided into two components: a general overview covering broad findings and offering recommendations, and country specific analyses that offer more targeted research and recommendations for each of the study countries.
Professional paper for the fulfillment of the Master of Development Practice and Master of Public Policy
Keywords: Barriers; Horticulture; Women